2017
DOI: 10.1111/1748-8583.12135
|View full text |Cite
|
Sign up to set email alerts
|

The glass ceiling in context: the influence of CEO gender, recruitment practices and firm internationalisation on the representation of women in management

Abstract: This study examines macro‐level organisational determinants of women in management. Specifically, we examined organisational characteristics and strategies, including firm levels of internationalisation, firm foreign ownership, chief executive officer gender and the active recruitment of women, as predictors of an organisation's level of representation of women in management. Results from a survey of 278 firms indicated that the presence of a female chief executive officer and an organisation's active recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 92 publications
(123 reference statements)
1
68
0
6
Order By: Relevance
“…Female CEOs and female-biased recruitment strategies are significantly more favorable for women to become managers. However, these studies also found that corporate internationalization and foreign investment have a negative impact on female senior managers [7]. Moreover, the subsidiaries of parent companies and companies with trade unions have a negative impact on female senior managers [24].…”
Section: Impact Of Environment On Ceo Gendermentioning
confidence: 96%
See 2 more Smart Citations
“…Female CEOs and female-biased recruitment strategies are significantly more favorable for women to become managers. However, these studies also found that corporate internationalization and foreign investment have a negative impact on female senior managers [7]. Moreover, the subsidiaries of parent companies and companies with trade unions have a negative impact on female senior managers [24].…”
Section: Impact Of Environment On Ceo Gendermentioning
confidence: 96%
“…This means that the selection of CEO is a major strategic decision that affects the development of the company. During the process of research on female executives, corporate characteristics play a key role in accounting for women's entry into management [7]. At the same time, the selection and appointment of senior executives is a typical strategic behavior and organizational result that is subject to the level of industry and social and economic development.…”
Section: Definition and Composition Of The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent members help with monitoring the management and providing an independent point of view. Ng and Sears (2017) report that firm ownership affects the inclusion of women in corporations and women inclusion is higher where there is a female CEO.…”
Section: Corporate Governance and The Glass Ceilingmentioning
confidence: 99%
“…The most remarkable transformation was that women are not just competing men in managerial cadre and entrepreneur activities, they started to show them to India's Business World through their achievements. It is also to be noted that in some classes women are compelling (Ng and Sears 2017). Although the Indian women have made significant progress in attaining equality status legally.…”
Section: Introductionmentioning
confidence: 99%